Unconscious Desire for Communism - Oxana Timofeeva (Identities, 2015)
The question of what the community should be is a question of value and what ought to be; any attempt to answer this question leads us to discordant models of social organization, to an ideological quarrel about how to rebuild humanity. The community appears as a gathering of people, large or small, but certainly different from a group, a collective, a society – in terms of its density or the character of its objectives, its anatomy or teleology. As we are told, the community is not a group, not a collective, no – and it is not a nation, not a people – but it is also not a crowd or a mass. The specter of communism hangs in the common and unappropriated air. The very name swears an oath of allegiance to the idea of the community. Communism is the society of the community, what is common and belongs to no one, but we will never agree on the subject of whether this principle coincides with or opposes democracy. Thus the specter of communism, having appeared out of the air, disperses into it as well. Communism is humanity’s memory of what has not yet happened. In this way it resembles a dream – you never know when the idyll might turn into a nightmare.